Current Trends In Turkısh Orthodontıcs - Funda Çırak; Metin Orhan; Serdar Üşümez; Enis Güray (Galenos Yayinevi, 2002)
The aim of this study was 1) to outline a portrait of current orthodontic practice in Turkey, 2) to interpret yielded factors that affect the preferences of Turkish orthodontists. 3) to contribute improvement and progress of orthodontics by detecting any possible deficiencies in Turkish orthodontics and. 4) to constitute a reference for the future national and/or international surveys to make possible the evaluation of changes in Turkish orthodontics. The study composed of a comprehensive questionnaire survey performed to find out the current diagnostic and therapeutic trends in Turkish orthodontics. The subgroups of data collected were about 1) personal information, 2) diagnostic records. 3) fixed appliance therapy. 4) functional treatment, intraoral and extraoral appliances. 5) finishing and retention, 6) orthognathic surgery. 7) clefts of the lip and palate and 8) temporomandibular joint. The questionnaire was sent to 225 members of the Turkish Orthodontic Society. The number of returned questionnaires was 122 with a return rate of 54,2. The collected data was used to draw a current portrait of orthodontics in Turkey. The study was concluded with comparison and discussion of data with the results of similar studies performed in other countries.